The employee experience’s paradigm applicability in relation to hybrid and remote working - Król, Małgorzata; Karczewska, Monika (Scientific Papers of Silesian University of Technology. Organization and Management Series, 2024)
Purpose: The purpose of the study is to identify instruments for shaping positive employee experience in hybrid and remote working environments. The following research questions were formulated: Can the experience modules – sensory, emotional, intellectual, behavioural and relational – be used to explore the possibility of shaping the positive employee experience of hybrid and remote employees? Using the experience modules, can the supervisor shape the positive experience of hybrid and remote employees?, Are there differences between the possibility of shaping the positive experience of hybrid and remote employees? Design/methodology/approach: A critical analysis of the literature, a diagnostic survey method and a statistical method were used to answer the researcher's questions. The subject of the study is instruments for shaping a positive employee experience in hybrid and remote working environments. Findings: The results of the study confirmed that the sensory, emotional, intellectual, behavioural and relational experience modules can be used as instruments to shape positive hybrid and remote employee experience. They also showed differences in the assessment of the applicability of the different instruments to hybrid and remote employees. Research limitations/implications: A limitation of the study is the non-random sampling and the small number of respondents. However, despite these limitations, the study may inspire further in-depth research into the (digital) employee experience issue. Practical implications: On the basis of the study conducted, recommendations of a practical nature can be made regarding the possibilities of shaping a positive employee experience for hybrid and remote employees. The proposed catalogue of instruments may be useful to those in managerial roles who recognise the need to shape the employee experience of hybrid and remote employees. Managers should be aware of the importance of positive employee experiences for human resource management practice, especially for attracting valuable employees, retaining and developing them, motivating them to work and increasing their commitment. Originality/value: The issue of employee experience is relatively new and rarely addressed by researchers in Poland. The study extended the research on employee experience to hybrid and remote employees. The results obtained contribute to the literature on employee experience, hybrid working and remote working. They provide a better understanding of the differences regarding the possibilities for shaping the employee experience of hybrid and remote employees. They can be of value to both theoreticians and practitioners of human resource management. Keywords: employee experience, digital employee experience, hybrid work, remote work. Category of the paper: Research paper.